The Role of Financial Management in Supporting The Effectiveness of Revenue in The Employee Service Cooperative of The Republic of Indonesia (Koperasi Jasa Pegawai Republik Indonesia) University of Brawijaya - Yeti Bota Muda; Elly Lestari; Moch Nurhidayat (International Research & Development for Human Beings (IRDH), 2025)
The purpose of this study was to find out how financial management supports the income effectiveness of the Employee Services Cooperative of the Republic of Indonesia at the University of Brawijaya Malang., Method: Three informants, general managers, general workers, and financial employees, participated in this qualitative investigation. The results of the interviews were used to collect research data. Data analysis: The chosen approach is descriptive data analysis. The collected data is analyzed by classifying, combining, and displaying the results of interviews to explain the phenomenon that occurs. Results and discussion: The results of the study show that regular recording of daily transactions and the preparation of monthly financial reports are two aspects of the implementation of financial management of the Employee Service Cooperative of the Republic of Indonesia that support the effectiveness of income at the University of Brawijaya Malang.